The Lure of Aggregates and the Pitfalls of the Patriarchal Perspective: A Critique of the High Wage Economy Interpretation of the British Industrial Revolution. - Humphries, J (Nuffield College (University of Oxford), 2011)
The newly dominant interpretation of the British industrial revolution contends that Britain was a high wage economy (HWE) and that the high wages themselves caused industrialization by making profitable labour-saving inventions that were economically inefficient in the context of other relative factor prices. Once adopted these macro inventions put Britain on a growth path that transcended the trajectories associated with more labour-intensive production methods. This account of the HWE economy is misleading because it focuses on men and male wages, underestimates the relative caloric needs of women and children and bases its views of living standards on an ahistorical and false household economy. A more realistic depiction of the working-class family in these times provides an alternative explanation of inventive and innovative activity based on the availability of cheap and amenable female and child labour and thereby a broader interpretation of the industrial revolution.